Can Neuroscience Assist Us in Constructing Better Patterns of Economic Decision-Making? - Lăzăroiu, George; Pera, Aurel; Ștefănescu-Mihăilă, Ramona O.; Mircică, Nela; Negurită, Octav (Frontiers in Behavioral Neuroscience, 2017)
We draw on outstanding research (Sanfey et al., 2006; McCabe, 2008; Bernheim, 2009; Camerer, 2013; Radu and McClure, 2013; Declerck and Boone, 2016) to substantiate that neuroeconomics covers the investigation of the biological microfoundations of economic cognition and economic conduct, attempts to prove that a superior grasp of how choices are made brings about superior expectations regarding which options are selected, preserves the strictness of economic analysis in defining value-based decision, and associates imaging techniques with economic pattern to explain how individuals decide on a strategy taking into account various possible choices. Neuroeconomics is adequately prepared to regulate the notion of how choices are determined by mental states. The position that will be elaborated in this article is that neuroeconomic patterns are enabled and enhanced in descriptive capacity by psychological outcomes and substantiated in biological processes. Advancement in neuroeconomics takes place when outcomes from distinct procedures are coherent with an ordinary mechanistic clarification of what generates choice, construed by a computational pattern. We will develop this point further by proving that economics improves the concerted effort of neuroeconomics by using its observations in the various results that may stem from the planned and market interplays of diverse participants, and via a series of accurate, explicit, mathematical patterns to construe such interplays and results. Neuroeconomics experiments employ a mixture of brain imaging/stimulation tests advanced in the cognitive neurosciences and microeconomic systems/game theory tests advanced in the economic sciences. Our analyses indicate that neuroeconomics aims to employ the supplementary input gained from brain investigations, associated with the decision maker’s selection, with the purpose of better grasping the cogitation process and to utilize the outcomes to enhance economic patterns.